(untitled) (Journal of Innovative Counseling : Theory, Practice, and Research, 2024)
This study aims to test the goodness of the Psychological Well-Being Scale Psychological Well-Being Scale adapted as a psychological measurement tool in college students. Research this research uses a mixed methodology method, namely combining qualitative and quantitative approaches. Qualitative and quantitative approaches. Qualitative methods are carried out when conducting the stages of translation and expert judgment. While the quantitative method was conducted during the data analysis process. The research was conducted in 5 universities in Tasikmalaya. Tasikmalaya by taking research subjects, namely students who were determined through Probability Sampling, namely with Simple Random Sampling technique. Sampling technique, the research instrument used is the Psychological Well-Being Scale. Psychological Wellbeing Scale the results showed empirically, that the Psychological Well-Being Scale is suitable for use as a psychological measurement tool for students in college students.